1999
DOI: 10.1177/089686089901902s62
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Peritoneal Rest on Peritoneal Transport and Peritoneal Membrane Thickening in Continuous Ambulatory Peritoneal Dialysis Rats

Abstract: Objective To evaluate the effects of peritoneal rest on peritoneal transport and morphology in a rat model of peritoneal dialysis. Design Twenty-four rats (Sprague-Dawley, male, 250 300 g) were divided into three groups: group 1 (control, n = 6) without dialysis, group 2 (n = 9) sacrificed immediately after 3 weeks of dialysis, and group 3 (n = 9) sacrificed after 4 weeks of peritoneal rest after 3 weeks of dialysis. Both dialysis groups were dialyzed twice daily with an intraperitoneal instillation volume of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 5 publications
1
30
0
Order By: Relevance
“…In a separate study, Rodrigues et al observed a recovery in ultrafiltration following peritoneal rest in 8 of 12 PD patients who had developed hyperpermeability [ 250 ]. In experimental models of PD, a period of 4–12 weeks of peritoneal resting was associated with a marked reduction in peritoneal fibrosis and angiogenesis, and complete remesothelialization of the peritoneal membrane [ 251 , 252 ].…”
Section: Potential Role Of Mesothelial Cell Transplantation and Gementioning
confidence: 99%
“…In a separate study, Rodrigues et al observed a recovery in ultrafiltration following peritoneal rest in 8 of 12 PD patients who had developed hyperpermeability [ 250 ]. In experimental models of PD, a period of 4–12 weeks of peritoneal resting was associated with a marked reduction in peritoneal fibrosis and angiogenesis, and complete remesothelialization of the peritoneal membrane [ 251 , 252 ].…”
Section: Potential Role Of Mesothelial Cell Transplantation and Gementioning
confidence: 99%
“…Several animal models of PF or peritoneal sclerosis have been used in intervention studies. These include chlorhexidine gluconate-induced models (19); chronic exposure to 4.25% glucose-based PD solution with or without renal failure (13,60), PD solution with LPS (26,33), or acidic PD solution (38); adenovirus-mediated gene transfer of transforming growth factor-␤ (TGF-␤) models (31,32); and acute bacterial peritonitis models with bacteria originating from skin flora (5) or with Staphylococcus epidermidis (18). However, these bacterial peritonitis models were mainly used to elucidate the mechanisms of inflammation in the membrane and of acute membrane failure.…”
mentioning
confidence: 99%
“…Peritoneal biopsy offers useful information about membrane morphology, but no standard method exists to adequately assess peritoneal morphology (5-10). Measurements of peritoneal thickness vary from section to section in the same tissue sample.…”
Section: Discussionmentioning
confidence: 99%